Pembagian Royalti Kekayaan Intelektual Sebagai Objek Harta Bersama Pasca Perceraian: Perspektif Hukum Positif dan Hukum Islam - Siregar, Bismar (Judge : Jurnal Hukum, 2025)
Divorce often triggers joint property division issues, including copyright royalties which have high economic value. Intellectual property rights (IPRs), including copyrights, play a role in protecting innovation, driving the economy and knowledge transfer in the modern era. Copyright, as part of IPR, protects and encourages creativity by providing economic incentives through royalties and joint property. This research is a library research, which is done by collecting, analyzing, and interpreting narratives comprehensively on document data to obtain a complete, comprehensive and holistic insight into intellectual property rights as an object of joint property. The results of this study found that according to Law Number 1 of 1974 concerning Marriage, Article 35 states that intellectual property rights obtained during marriage can become joint property. In addition, each spouse continues to control the innate property of each husband and wife as well as the property they each obtain as a gift or inheritance, as long as it is not specified otherwise in the marriage agreement. This is also clarified in Article 119 BW Burgelijk Wetboek, which says that the husband and wife's property is immediately united at the time of the formation of the marriage bond. The enactment of KHI, which is based on the legal instrument of Presidential Instruction Number 1 of 1991, is considered no longer relevant to follow the development of applicable law in Indonesia. The provisions regarding joint property, IPRs has not explicitly explained the status of IPRs as joint property.